Electrical stimulation for the treatment of spinal cord injuries: A review of the cellular and molecular mechanisms that drive functional improvements - Dorrian, Ryan M.; Berryman, Carolyn F.; Lauto, Antonio; Leonard, Anna V. (Frontiers in Cellular Neuroscience, 2023)
Spinal cord injury (SCI) is a devastating condition that causes severe loss of motor, sensory and autonomic functions. Additionally, many individuals experience chronic neuropathic pain that is often refractory to interventions. While treatment options to improve outcomes for individuals with SCI remain limited, significant research efforts in the field of electrical stimulation have made promising advancements. Epidural electrical stimulation, peripheral nerve stimulation, and functional electrical stimulation have shown promising improvements for individuals with SCI, ranging from complete weight-bearing locomotion to the recovery of sexual function. Despite this, there is a paucity of mechanistic understanding, limiting our ability to optimize stimulation devices and parameters, or utilize combinatorial treatments to maximize efficacy. This review provides a background into SCI pathophysiology and electrical stimulation methods, before exploring cellular and molecular mechanisms suggested in the literature. We highlight several key mechanisms that contribute to functional improvements from electrical stimulation, identify gaps in current knowledge and highlight potential research avenues for future studies.